Visualizations of the small military drone: normalization through 'naturalization'. Issue 4 (2nd October 2022) - Jackman, Anna
ABSTRACT: We are in the midst of a global turn to the drone. Responding to the 'unmanning' of contemporary warfare, interdisciplinary scholarship has interrogated the human operators and non-human actors underpinning the drone, and their wide-ranging ethical, geopolitical, and legal implications. A key facet of extant drone debates surrounds drone vision – both as it operationally visualizes and is fetishized. While comparatively nascent, scholars have begun to explore how drones are instead visualized across particular media. In this article I identify two lacuna within extant drone scholarship: first a lack of attentiveness to small military drones, which while comprising the majority of global military arsenals remain comparatively absent from scholarly analysis; and second, a need to attend to a greater diversity of visual representations of the drone. In response, this article explores promotional visualizations of small military drones as they are ethnographically-encountered at a key site through which their usage is compelled and their functioning enabled – the defence tradeshow. In so doing, I identify three central frames through which the drone is repeatedly represented therein. I argue that these frames both engage and employ visual conventions associated with 'nature' and the 'natural' in order to 'naturalize' and normalize the drone in as-yet unaccounted ways. Approaching the drone through the current, yet under-examined, visual milieu of the defence environments in which it is promoted, the article contributes to both interdisciplinary drone scholarship, and literatures exploring the visual cultures of militarism more widely.